PERDAGANGAN BARANG DAN PENGGUNAAN ENERGI TERBARUKAN SEBAGAI DETERMINAN PRODUK DOMESTIK BRUTO DI BELIZE - Bhenu Artha; Ainun Hertikasari (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect of trade in goods and the use of renewable energy on gross domestic product in Belize. This study uses data from the World Bank for the period 1990-2015. The results of the data analysis show that together the variables of trade in goods and the use of renewable energy have a significant positive effect on GDP. Partially, the variable trade in goods has a significant negative effect on GDP. The variable use of renewable energy partially does not affect GDP. Keywords: merchandise trade, renewable energy consumption, gross domestic product, Belize